Security in a small nation Scotland, democracy, politics - Neal, Andrew W., 1978-; Open Book Publishers (Open Book Publishers, 2017)
"The 2014 Referendum on Scottish independence sparked debate on every dimension of modern statehood. Levels of public interest and engagement were unprecedented, as demonstrated by record-breaking voter turnout. Yet aside from Trident, the issue of security was relatively neglected in the campaigns, and there remains a lack of literature on the topic. In this volume Andrew Neal has collated a variety of interdisciplinary perspectives on security and constitutional change in Scotland and the UK, including writing from experts in foreign policy analysis, intelligence studies, parliamentary studies, and journalism. Security in a Small Nation provides an illuminating analysis of the politics of security. Its authors reflect on a number of related issues including international comparisons, alliances, regional cooperation, terrorism, intelligence sharing, democratic oversight, and media coverage. It has a particular focus on what security means for small states and democratic politics. The book draws on current debates about the extent of intelligence powers and their implications for accountability, privacy, and human rights. It examines the foreign and security policy of other small states through the prism of Scottish independence, providing unique insight into the bureaucratic and political processes associated with multi-level security governance. These contributions provide a detailed picture of the changing landscape of security, including the role of diverse and decentralised agencies, and new security interdependencies within and between states. The analysis presented in this book will inform ongoing constitutional debates in the UK and the study of other secessionist movements around the world. Security in a Small Nation is essential reading for any follower of UK and Scottish politics, and those with an interest in security and nationhood on a global scale."--Publisher's website.
ESRC Report 1. Assessing security governance in the UK and Scotland under current arrangements -- ESRC Report 2. The threat environment of the UK and Scotland in the context of the UK National Security Strategy -- ESRC Report 3. Security, intelligence and EU cooperation: Scotland's comparator countries -- ESRC Report 4. Intelligence and security oversight in an independent Scotland.
"This book is the product of a seminar series funded by the UK Economic and Social Research Council entitled "Security in Scotland, with or without constitutional change", which ran from 2013-2015 at the University of Edinburgh. The reports from this seminar series can be found on the title page [of this book under Additional Resources] on the Open Book Publishers website ..."--Acknowledgements, unnumbered page viii.
Available through Open Book Publishers.
Includes bibliographical references.
Mode of access: World Wide Web.
Keywords: Intelligence service -- Scotland; International relations -- Scotland; National security -- Scotland